Unusual Recto-colonic Tubular Duplication in a Female Neonate - Nahla, Kechiche; Farhani, Rabeb; Lamiri, Rachida; Mekki, Mongi; Belguith, Mohssen; Nouri, Abdellatif (Journal of Neonatal Surgery, 2019)
Complete tubular colonic duplication is exceedingly rare. A second ectopic opening in the perineum other than a normally cited anus could be an unusual presentation. We report an unusual case of recto-colonic duplication in a 16-day-old girl who presented with fecal discharge from a vestibular opening in addition to a normally situated anus. The diagnosis of total recto-colonic tubular duplication associated with a rectovestibular fistula and a normal anus was confirmed by barium enema and computed tomography scan with double contrast. At operation, we performed a long transanal incision of the common septum to create an anastomosis between the normal and duplicated colon with complete submucosal excision of the rectovestibular fistula. The patient was doing well at 3-year follow-up examination.